1998
DOI: 10.1029/98jc01269
|View full text |Cite
|
Sign up to set email alerts
|

Inversion of pack ice elastic wave data to obtain ice physical properties

Abstract: Abstract. Geophones mounted on floating ice sheets can potentially provide data for a robust method to monitor mechanical properties of the ice. The technique relies on the measurement and inversion of low-frequency elastic waves propagating in the ice. To test this hypothesis, several geophone systems were deployed on the Arctic ice as part of the Office of Naval Research Sea Ice Mechanics Initiative (SIMI), including a winter-over system of 20 triaxial geophones at the fall 1993 SIMI camp. An inversion techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2002
2002
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 16 publications
0
37
0
Order By: Relevance
“…Good sourcebearing estimates were obtained, with average absolute bearing errors of 5°-11°per geophone. Polarization filtering was shown to significantly improve the bearing estimates by removing S H particle motion, and may also be useful for determining ice properties from elastic waves, 15 although this approach was not applied here. Overall, the results in this paper indicate that ice-mounted geophones can provide useful bearing estimates for acoustic sources in Arctic waters.…”
Section: Summary and Discussionmentioning
confidence: 98%
“…Good sourcebearing estimates were obtained, with average absolute bearing errors of 5°-11°per geophone. Polarization filtering was shown to significantly improve the bearing estimates by removing S H particle motion, and may also be useful for determining ice properties from elastic waves, 15 although this approach was not applied here. Overall, the results in this paper indicate that ice-mounted geophones can provide useful bearing estimates for acoustic sources in Arctic waters.…”
Section: Summary and Discussionmentioning
confidence: 98%
“…Elastic parameters were set to q ¼ 910 kg m À3 (ice density), and ¼ 0:33 (Poisson coefficient). Two values of Young's modulus are used: our preferred value of E ¼ 7:2 GPa (Stein et al, 1998) as shown in thick lines, and a larger value of E ¼ 9:7 GPa, shown in thin line. This value was given by Pounder and Langleben (1964) for low porosity sea ice with less than 10% of brine content.…”
Section: Datamentioning
confidence: 99%
“…In seismic studies, the latter can be constrained by estimating the non-dispersive velocities of longitudinal plate (LP) and horizontally polarized shear (SH) waves. Several field experiments have been conducted in the past to exploit these seismic methods (Yang and Giellis, 1994;Stein et al, 1998), see also Anderson (1958) for a review of earlier works. The typical experimental set-up involves the use of active source, e.g., hammer blows or shots; these methods therefore require human assistance and are thus non-autonomous.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations